THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION TECHNIQUES ON REDUCING SYSTOLE BLOOD PRESSURE IN ELDERLY PEOPLE WITH HYPERTENSION - Fauziah, Wardah; Mahayu Adiutama, Novian; Krisna, Teja (Universitas Airlangga, 2024)
Introduction: Hypertension is a disease that is often not felt but can have serious consequences for health. One way to prevent and overcome hypertension is using non-pharmacological therapy, one of which is the progressive muscle relaxation technique which is useful for lowering blood pressure. This study aims to analyze the effect of progressive muscle relaxation techniques on reducing systolic blood pressure in elderly people with hypertension. Methods: The method used is quantitative research with a pre-post test quasi-experimental research design with a control group. Sampling using a simple random sampling technique with a total of 60 respondents divided into 2 groups, namely, 30 intervention groups and 30 control groups. Data analysis using the Independent Sample T-test parametric test. Results: The results showed the average value of pre-test blood pressure in the intervention group was 157 mmHg and the control group was 149 mmHg, while in the post-test the intervention group after being given the progressive muscle relaxation technique was 136 mmHg and the control group was 134 mmHg. Data analysis using the Independent Sample T-test test obtained a p-value of 0.000 which indicates the effect of progressive muscle relaxation techniques on the elderly with hypertension. Conclusions: Therefore, it can be concluded that progressive muscle relaxation techniques can have an effect on reducing systolic blood pressure in the elderly with hypertension and it is recommended that this study be used as a reference material and implementation in performing progressive muscle relaxation techniques to prevent and control hypertension.